Dead or alive - Clancy, Tom with Blackwood, Grant; Grant Blackwood (New York : Penguin Group, USA, 2010)
It is called the Campus. It was secretly created under the administration of President Jack Ryan, its sole purpose to hunt down, locate, and eliminate terrorists and those who protect them, at will, without sanction or oversight. A self-sufficient entity, it has no official connection to the American government--a necessity in a time when those in power consider themselves above such arcane concepts as loyalty, justice, and right or wrong.